Redescription of female specimens of Corycaeus (Corycaeus) crassiusculus Dana and Corycaeus (Onychocorycaeus) catus Dahl (Poicilostomatoida: Corycaeidae) from Kavarathi Atoll, Lakshadweep Island, India. - Radhika, S.R., S. Bijoy Nandan & M. Harikrishnan (Biosystematica, 2015)
In 1929 and 1911, the female specimen of Corycaeus crassiusculus (Dana, 1848) and Onychocorycaeus catus (Dahl 1894) was first recorded in the Indian ocean by Farran and in the Arabian sea by Sewell in 1947. The two species are redescribed by a combination of morphological characteristics as follows in females (1) ornamentation of the first endopodal segment of the antenna of C. crassiusculus (2) overlapping of genital segment on anal segment at the dorsal margin in C. crassiusculus (3) distal margin of the genital and anal somite ornamented with spines ventrolaterally in both (4) presence of four spines in the third exopodal segments of first, second & third swimming leg in O. catus (5) length to width of 1st endopodal segment of the antenna (6) length ratio of coxal seta: 1st endopodal seta; (7) in P1 to P3 exp-3, length ratio of terminal spine to distal segment and to outer distal spine; (8) in P4 exp-3, length ratios of terminal spine to proximal spine and to distal segment. A comparison of the morphological variability with existing descriptions from other regions have also been provided.